The role of angiogenin in pT1‐T2 tongue carcinoma neo‐angiogenesis and cell proliferation: an exploratory study. (25th February 2013) - Marioni, Gino; Staffieri, Alberto; Fasanaro, Elena; Stramare, Roberto; Giacomelli, Luciano; Bernardi, Elena; Val, Matteo; Stellini, Edoardo; de, Cosimo; Blandamura, Stella
<x xml:space="preserve">Abstract</x> Background Angiogenin (ANG) is a member of the ribonuclease superfamily and of medical interest largely because it supports the growth of primary and metastatic malignancies. This study is the first to investigate the potential role of ANG in tongue carcinoma neo‐angiogenesis and cancer cell proliferation. Methods Angiogenin expression (in carcinoma cells and endothelial intratumor vessel cells), CD105‐assessed micro‐vessel density (MVD), and MIB‐1 expression were correlated with prognostic parameters in 28 primarily consecutively operated pT1‐T2 tongue carcinomas (squamous cell carcinoma [SCC]). Whenever feasible, a computer‐based image analysis system was used for the immunohistochemical reaction analysis. Results No significant correlations emerged between ANG expression in the tongue carcinoma cells or endothelial intratumor vessel cells and tongue SCC recurrence rate or disease‐free survival (DFS). ANG expression was also unrelated to CD105‐assessed MVD or MIB‐1 expression. Conversely, CD105‐assessed MVD correlated directly with recurrence rate (P = 0.02) and DFS was significantly shorter in cases with CD105‐assessed MVD >167 micro‐vessels/mm2 than in those with CD105‐assessed MVD ≤167 micro‐vessels/mm2 (P = 0.042). Conclusions Our results support the hypothesis that CD105‐assessed MVD would be a valuable parameter for predicting which patients with tongue SCC are at greatest risk of disease recurrence. Despite our study results, the role of ANG in tongue carcinoma warrants further investigation in larger series.